Multistage alteration, mineralization and ore–forming fluid properties at the Viper (Sappes) Au–Cu–Ag–Te ore body, W. Thrace, Greece. - Kilias, S.P.; Naden, J.; Paktsevanoglou, M.; Giampouras, M.; Stavropoulou, A.; Apeiranthiti, D.; Mitsis, I.; Koutles, Th.; Michael, K.; Christidis, C. (Bulletin of the Geological Society of Greece, 2013)
The mineralogy of ore and hydrothermal alteration of the high-sulfidation enargite–Au–Ag–Te Viper (Thrace) orebody, and fluid inclusions, were studied in drillcore samples. The hydrothermal system has evolved through several stages from pre-ore advanced argillic I+vuggy silica alteration, ore-stage advanced argillic II+vuggy silica alteration and silicification that has developed to argillic alteration (sericite)+silicification through pH increase, and a return to acid conditions as crosscutting post-ore advanced argillic alteration III+silicification. Ore is characterized by early barren pyrite I corroded by: (i) enargite–Au± complex Pb–Bi–Cu sulfosalts, tellurides and selenides, coexisting with euhedral quartz, and (ii) zoned pyrite II distinguished by anomalous concentrations of Au, Cu, As, Te, Bi, Pb, Se, within vuggy quartz. High-grade gold ore is also intergrown with late brecciacementing and vein-type epithermal-like banded quartz+ pyrite. These alteration and mineralization observations are consistent with the changing composition, water fugacity, and density of an expanding column of metal-laden magmatic vapor, combined with changes in structural permeability. Part of the enargite─Au─ quartz assemblages have been probably quenched from sulfosalt melt at high─temperatures (>575°C). End product of the enargite–sulfhide–silica crystallization sequence is the formation of high-grade epithermal quartz-gold colloformbanded ore during cooling and/or dilution/mixing down to 200°C.